Manual behavior in newborns and infants from birth to three months old - Priscilla Augusta Monteiro Ferronato; Edison de Jesus Manoel; Luiz Eduardo Pinto Bastos Tourinho Dantas (Elsevier, 2023)
Background: There is more to manual behavior in newborns and infants up to three months old than eye-hand coordination. Aim: In this study, we describe changes in the way infants, from birth to three months old, clutched a rod and propose that this might be related to active hands' exploratory behavior. Study design: Observational study which infants clutching behavior was collected during a two-minute session condition carried out in a lab quiet room. The infants were sitting on an adapted baby chair when a rubber rod, similar in size and shape to an adult's finger, was placed into the infants' palms inducing a palmar grasp followed by clutching behavior. Subjects: Fifty-one typical developed full-term infants took part in the study and they were divided into 4 groups: three-day-old (n = 17), one-month-old (n = 9), two-month-old (n = 11), and three-month-old (n = 14). Outcome measures. The rod into infant's hand had a built-in transducer that allowed the measurement of hand pressure used to calculate the mean and standard variation (SD) for multiple dependent variables. Results: A Kruskal-Wallis analysis revealed the age effect for frequency of clutches, pressure standard deviation and mean clutch duration. We found that, from birth to 3 months old, there was a clear trend which showed that as infants age they clutch more often, faster, and with increasing variability. Conclusions: We discussed these results as being indicators that during the first three months infants increase their behavior variability to explore objects, learn about the functions of their body, and to identify regularities between actions and their consequences when is given the opportunity.